DISSOLUTION PROFILE OF A TRADITIONAL THAI ANTIHYPERTENSIVE HERBAL RECIPE IN VARIOUS PREPARATIONS - Vutthipong, Arthimond; Saingam, Worawan; Panrat, Tanate; Charoonratana, Tossaton (Interprofessional Journal of Health Sciences, 2023)
A dissolution test was developed for a traditional Thai antihypertensive herbal recipe (TTAH) in various preparations. Three different formulations, such as pill, tablet, and capsule, were prepared and evaluated for their release profile in which piperine was chosen as a marker in dissolution study. The test was performed using paddle method with 50 rpm and dissolution medium composed of 0.2 M phosphate buffer pH 7.4. The sampling times were 5, 10, 15, 30, and 60 min. Liquid chromatography mass spectrometry (LC-MS) was used as a tool to determine amount of piperine. Different piperine release profiles were achieved and it was found that the reported method in this article was suitable for dissolution study only in capsule and tablet preparations.